Training Guide on Integrated Pest Management in Tobacco 2016
DOI: 10.1079/9781786392381.0011
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the training guide.

Abstract: A lack of knowledge on integrated pest management (IPM) amongst the farmers (and sometimes field technicians) can be a barrier to responsible management and use of crop protection agents (CPAs), such as insecticides, fungicides and herbicides. Hence, addressing any knowledge gaps is a necessary first step in order for changes in behaviour to take place. This Training Guide provides training material to address training needs and offers guidance on how to adapt the core material to local conditions through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A market survey of biopesticides carried out in 2016 for 20 countries where tobacco is grown identified approximately 50 different biopesticide AS that are permitted to be used in tobacco (Bateman et al, 2016). In a follow-up survey, leaf suppliers operating in even more countries indicated that they have experience with over 60 biopesticide AS, and would recommend 25 of those AS to others for use (Grunder and Bateman, 2017).…”
Section: Determining Which Biopesticides Are Allowed For Use In a Coumentioning
confidence: 99%
“…A market survey of biopesticides carried out in 2016 for 20 countries where tobacco is grown identified approximately 50 different biopesticide AS that are permitted to be used in tobacco (Bateman et al, 2016). In a follow-up survey, leaf suppliers operating in even more countries indicated that they have experience with over 60 biopesticide AS, and would recommend 25 of those AS to others for use (Grunder and Bateman, 2017).…”
Section: Determining Which Biopesticides Are Allowed For Use In a Coumentioning
confidence: 99%